The Implementation of Springate, Altman, Grover and Zmijewski Models in Measuring Financial Distress - Supitriyani; Astuti; Khairul Azwar (Asosiasi Dosen Akuntansi Indonesia, 2022)
Companies that have improved company performance will have good prospects in the future. In addition, the company also needs some good strategy and planning to stay afloat in running its business. One of the strategies carried out by the company is to avoid the occurrence of a level of financial difficulties (financial distress). The goal of the study was to determine bankruptcy predictions and find out the most accurate methods for measuring bankruptcy among Springate, Altman, Grover and Zmijewski models. The data collection techniques used are documentation techniques while the data analysis techniques used are qualitative descriptive analysis techniques and comparative analysis techniques. The results showed that there was a predictive difference between Springate, Altman, Grover and Zmijewski models in predicting bankruptcy (financial distress). The Altman model is the most accurate prediction model in predicting bankruptcy with the highest degree of accuracy which then continued the Springate model, Grover model and finally the Zmijewski model. The renewal of previous research is to use four methods of predicting bankruptcy at once, different research objects and times from previous researchers